Hydrogeochemical Evolution and Control Mechanism of Underground Multiaquifer System in Coal Mine Area - Qiding Ju; Yu Liu; Youbiao Hu; Yuquan Wang; Qimeng Liu; Zitao Wang (Geofluids)
Mining activities interfere into the natural groundwater chemical environment, which may lead to hydrogeochemical changes of aquifers and mine water inrush disasters. The study of hydrogeochemical evolution processes of underground aquifers is helpful to the prevention and control of mine water inrush. The results show that the study area is mainly impacted by four hydrogeochemical processes: dissolution, cation exchange, desulfurization and reduction, and pyrite oxidation. The Cenozoic aquifers are dominated by carbonate dissolution and desulfurization. The Permian aquifers are impacted mainly by cation exchange and sulfate dissolution, followed by pyrite oxidation. The Carboniferous aquifers are mainly impacted by dissolving sulfate, followed by pyrite oxidation and cation exchange. The hydrogeochemical evolution of the aquifers was controlled by mining activities and tectonic changes, and a certain regularity in space. For the Cenozoic aquifers, sulfate dissolution and cation exchange increase from west to east, and desulfurization weakens. For the Permian aquifers, cation exchange and sulfate dissolution are stronger near synclines and faults, pyrite oxidation is enhanced, and desulfurization decreases from the middle to the east of the mining area. For the Carboniferous aquifers, there is a higher dissolution of rock salt, pyrite oxidation, and cation exchange from west to east, and the desulfurization effect weakens.